(untitled) (Universitas Scientiarum, 2021)
Phosphorus (P) is an essential nutrient for plant’s development, and its deficiency restricts crop yield. To meet P requirements in agricultural settings, a low-cost culture medium (MT11B) was designed in which a bioinoculant was produced consisting of three bacterial isolates capable of solubilizing P from phosphoric rock (PR). Pseudomonas sp., Serratia sp., and Kosakonia sp. exhibited P solubilization in SMRS1 agar modified with PR (5.0 g L-1), as source of inorganic P. Sowings by isolation were made of the three bacteria on DNAse- and Blood-agar to rule out pathogenicity. At the interaction tests, no inhibition halos were observed; demonstrating there was no antagonism among them, thus they were used to constitute a consortium. Growth curve (12 h) in MT11B demonstrated consortium grew in presence of PR, brewer’s yeast hydrolysate, and glucose at concentrations (2.5 g L-1) fourfold lower than those in SMRS1 (10.0 g L-1); obtaining phosphate solubilizing bacteria of (10.60 ± 0.08/ log10 CFUmL-1 and, at 6 h of culture, acid and alkaline phosphatase enzyme volumetric activities of 2.3 ± 0.8 and (3.80 ± 0.13) UP, respectively. The consortium, releasing phosphorus at a rate of (45.80 ± 5.17) mg L-1 at 6 h of production, was evaluated as bioinoculant in onion plots for five months. Plants receiving a treatment that included 500 mL (10 x 107 CFU mL-1) of bioinoculant plus 100 kg ha-1 of an organic mineral fertilizer exhibited the highest determined response variables (170.1 ± 22.2) mm bulb height, (49.4 ± 6.5) mm bulb diameter, (9.0 ± 1.8) g bulb dry weight, and 15.21 mg bulb-1 total phosphorus (p < 0.05).